Vasculature of the brain and cranial base variations in clinical anatomy - Grand, Walter; Hopkins, L. N.; Siddiqui, Adnan H.; Mocco, J. (Thieme, 2016)
Comprehensive variations of the vasculature at the Circle of Willis, cortical branches, and secondary arteriesRange and average measurements of the most critical vesselsHundreds of color photographs elucidate precise anatomical cadaver dissections Exquisite illustrations by Paul H. DresselThis richly illustrated, comprehensive anatomical resource is a must have for neurosurgeons, neuroradiologists, and neurologists. Whether you are a practicing clinician or resident, reading this book will greatly expand your "vision" and sharpen your perception